The Health Benefits of Foods Current Knowledge and Further Development - Claudia Salanță, Liana (IntechOpen, 2020)
The global market of foods with health claims remains highly dynamic and is predicted to expand even further. Consumers have become increasingly aware of the importance of consuming healthy foods in order to have a well-balanced diet and this has increased the demand for foods with health benefits. On the other hand, the food sector companies are trying to meet the new consumers' expectations while designing a variety of novel, enhanced products. Thus, understanding the potential uses of bioactive compounds in food products, the wide range of therapeutic effects, and the possible mechanisms of action is essential for developing healthier products. Covering important aspects of valuable food molecules, this book revises the current knowledge, providing scientifically demonstrated information about the benefits and uses of functional food components, their applications, and the future challenges in nutrition and diet.